Utilization Of Organic Waste To Become Eco-Enzyme In Developing Community Environmental Literacy - Yunus Abidin; Hana Yunansah; Dede Margo Irianto; Yusuf Tri Herlambang; Rahman Wahid (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Community service Program aims to develop the literacy environment of the community through the activities of the utilization of organic waste into eco-enzyme. Eco-enzyme to be one of the effective solutions in addressing the buildup of organic waste in the community and manage it into something more useful. Products that can be generated from the management of organic waste into eco-enzyme among others, is a liquid soap, toilet cleaner, air freshener, and water purification. In addition, the community service program is driven over the still low literacy communities is shown by the less skilled of the community in managing organic waste. The method used in the program of the community service is done using the method of the development of action research. The results of community service activities conducted in the Village of Pasir Biru, Cibiru District, Bandung City go according to plan and obtain the level of satisfaction of the partner.